2009
DOI: 10.1103/physreve.80.046317
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional supersonic nonlinear Schrödinger flow past an extended obstacle

Abstract: Supersonic flow of a superfluid past a slender impenetrable macroscopic obstacle is studied in the framework of the two-dimensional defocusing nonlinear Schrödinger (NLS) equation. This problem is of fundamental importance as a dispersive analogue of the corresponding classical gas-dynamics problem. Assuming the oncoming flow speed sufficiently high, we asymptotically reduce the original boundary-value problem for a steady flow past a slender body to the one-dimensional dispersive piston problem described by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
9

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 46 publications
(220 reference statements)
3
77
0
9
Order By: Relevance
“…which agrees with the asymptotic representation of a highly supersonic oblique GP soliton in [17]. Without loss of generality we consider the waves in the upper half-plane (a > 0), then it follows from (44) that 0 ≤ λ ≤ 1.…”
Section: It Is Instructive To Establish a Direct Asymptotic Corresponsupporting
confidence: 68%
See 4 more Smart Citations
“…which agrees with the asymptotic representation of a highly supersonic oblique GP soliton in [17]. Without loss of generality we consider the waves in the upper half-plane (a > 0), then it follows from (44) that 0 ≤ λ ≤ 1.…”
Section: It Is Instructive To Establish a Direct Asymptotic Corresponsupporting
confidence: 68%
“…The obtained solutions provide a basis for further studies connected with the description of dispersive shock waves observed in recent experiments [2] of the flow of a BEC past obstacles as well as in numerical simulations [17]. Some straightforward implications about the characteristic features of the wave patterns arising in the flow of a BEC past an obstacle have been made from the expressions for the slope a in the obtained asymptotic reductions of the full periodic solution.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations